Effects of interventions to manage dual practice (Protocol) - Kiwanuka, S. N.; Kinengyere, A. A.; Nalwadda, C.; Ssengooba, F.; Okui, O.; Pariyo, G. W. (Cochrane Database Syst Rev, 2010)
Holding two or more jobs, also referred to as dual practice in the healthcare setting, has been documented as a common practice in both developed and developing countries (Eggleston 2006; Gonzélez 2004; Rickman 1999; Roenen 1997).The practice refers to the holding ofmore than one job by a health professional. It may encompass health professionals working within different aspects of health such as allopathic medicine combined with traditional medicine or combining health related activities such as clinical practice with research (Ferrinho 2004). In most low and middle income countries (LMICs), dual practice refers to health professionals engaged in both public and private (health or non-health) related work (Ferrinho 2004). Non-health related dual practice has been reported as well with the engagement of health workers earning additional income, for example, in agricultural or other economic activities (Assimwe 1997; Roenen 1997).
Keywords: dual practice; medicine; health professional.